PORTABLE DEVICE AS A DIAGNOSTIC TOOL FOR MARFAN’S SYNDROME IN A REMOTE AREA: A CASE REPORT - Freire de Carvalho Espírito Santo, Yuri (Health and Society, 2023)
The Marfan’s syndrome is an autosomal dominant genetic disease that affects connective tissue, with an incidence of approximately one case for every 5000 individuals. Cardiovascular involvement often occurs in adulthood. As the most common manifestation of the syndrome, ascending aortic aneurysm frequently leads individuals to conditions of clinical emergencies, the emergency room and intensive care unit are a common sites for diagnosing cardiac disorders in patients with Marfan. In this article we find the case report of a 41-year-old patient with a history of chest pain, signs and symptoms of heart failure, admitted to the ICU, with phenotypic manifestations of the disease, whose aortic aneurysm was diagnosed during the initial examination of POCUS. As it is a relatively rare diagnosis, in a rural patient who until now was unaware of the diagnosis itself, the result of which was identified in a routine examination in the ICU, performed with a portable device, the ability to change the outcome of a disease with high morbidity and mortality with a simple exam, easy to access and with low training requirements in a highly complex unit, even in distant care units in a population with low socioeconomic status. This article aims to show how a simple examination, POCUS, performed with a handheld device, is able to identify complex, high-impact diseases.